Contents of the photo coverage of the Gulf Cup Championship on the pages of photojournalists on Instagram: An analytical study - Salman, Haneen Saad; Fawzi, Reem Adil (ALBAHITH ALALAMI, 2023)
This study intends to examine the content of photo coverage related to the Gulf Cup (Gulf 25) as presented by Iraqi photojournalists on Instagram between 02/01/2023 and 27/01/2023. Utilizing content analysis, the two researchers employed the survey method to evaluate 674 digital photos posted by seven photojournalists specializing in this sporting event, which concluded with the Iraqi team’s victory in the city of Basra. Key findings from the study include: 1. The Category "Photos from the Gulf Cup matches" predominated, accounting for 291 instances or 42.794% of the total. 2. Photojournalists exhibited a keen interest in capturing images of attending fans and documenting celebrations surrounding the Gulf Cup. 3. Notably, despite the presence of children with cancer and those with special needs at the Gulf Cup, the research observed minimal photographic coverage of this significant societal segment.